COMMERCIALIZATION OF MARKET INNOVATIONS AS EXCLUSIVE TASK OF INNOVATIVE MARKETING - Babukh, Ilona (My University, 2017)
The development of modern innovative economy requires greater use of potential of non-technical (institutional) innovations, especially promotional ones. Commercialization of market innovations is one of the most important conditions for sustainable economic development. Such development requires the active use of innovative marketing. As essentially defining task of marketing innovation, as well the source and means of its development is considered commercialization of market innovations – of goods and marketing approaches. Commercialization presupposes existence of inconsistent («nonlinear») links between tools of the innovative marketing: development of innovation, marketing researches, segmentation, and positioning and management lifecycle.
Комерціалізація ринкових інновацій як виняткове завдання інноваційного маркетингу
Keywords: marketing; innovation marketing; market innovation; commercialization; tools of commercialization; positioning; lifecycle management; segmentation